Accountability Myopia: Losing Sight of Organizational Learning - and Ebrahim, Alnoor (Nonprofit and Voluntary Sector Quarterly, 2005)
This article challenges a normative assumption about accountability in organizations: that more accountability is necessarily better. More specifically, it examines two forms of “myopia” that characterize conceptions of accountability among service-oriented nonprofit organizations: (a) accountability as a set of unconnected binary relationships rather than as a system of relations and (b) accountability as short-term and rule-following behavior rather than as a means to longer-term social change. The article explores the effects of these myopias on a central mechanism of accountability in organizations—evaluation—and proposes a broader view of accountability that includes organizational learning. Future directions for research and practice are elaborated.
Keywords: IMPORTANT